Critical analysis of the grammar activities.: Critical analysis of the grammar activities. - Majidova, Gulruh (Maktabgacha taʼlim jurnali, 2021)
Abstract: The article analyses three different grammar activities and their efficiency in teaching grammar. Moreover in order to achieve higher efficiency some suggestions are given concerning the use of those activities which will be helpful for EFL teachers to employ the activities in similar form during their classes.